1 Public Records of the Colony of Connecticut 138 (J. Hammond Trumbull ed., 1850) (enacted 1646) - (:unkn) unknown (My University, 1646)
("The Court [desires] that the Comissio[ners] should be [moved] that noe ]Ammuition] should be traded wth any that [live] out of the Jurisdictions in combination, whereby [it] might supply the Indeans. and that some consideration be taken to [restrain] Roade lland fro[m] trading w[i]th the in such kynd." [some antique spelling modernized])
Keywords: ENSLAVED PERSONS & OTHER MINORITIES